2018
DOI: 10.1016/j.jip.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Increased tolerance of Beauveria bassiana and Metarhizium anisopliae conidia to high temperature provided by oil-based formulations

Abstract: The influence of the temperature of aqueous conidial sprays on conidial viability and virulence against Diatraea saccharalis was evaluated for pure conidia, rice + fungus (technical concentrates) and oil-based formulations of Beauveria bassiana s.s. and Metarhizium anisopliae s.s. under laboratory conditions. The fungal preparations were suspended in water and maintained at 26 °C, 36 °C and 46 °C for one, four and six hours. Conidial viability was determined by plating aliquots of each suspension onto PDA medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 51 publications
2
28
0
2
Order By: Relevance
“…However, formulation techniques have been shown to increase EPF viability under stressful environmental field conditions. For example, emulsifiable oilbased formulations increased fungal tolerance to high temperatures (Oliveira et al 2018), whilst addition of vegetable oils to conidial suspensions increased protection against the harmful effects of UV (Kaiser et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, formulation techniques have been shown to increase EPF viability under stressful environmental field conditions. For example, emulsifiable oilbased formulations increased fungal tolerance to high temperatures (Oliveira et al 2018), whilst addition of vegetable oils to conidial suspensions increased protection against the harmful effects of UV (Kaiser et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Without protective formulations, EPF are poorly active against targeted insects under field conditions (Kaiser et al., 2020). Studies have shown that oil‐based formulations can provide protection from unsuitable weather conditions (de Oliveira et al., 2018) and result in a greater impact on insect pests (Kaiser et al., 2020; Luz & Batagin, 2005). In this study, vegetable oil, canola oil (Codacide ® ) and olive oil were able to protect the conidia of both fungal species from solar UV radiation under glasshouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Conidia were considered germinated (i.e. viable) if they had a germ tube longer than their diameter after 16 h of incubation at 26 ± 0.5 °C with a 12 h photoperiod 26 . Conidial viability was checked before each experiment and reached 90% of germination in all cases before the formulation experiments unless expressly stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to unformulated conidia, oil formulation can elevate the virulence and shelf life of formulated conidia against whitefly 23 and grasshoppers 24 . Different carriers, including mineral oil 25 and soybean oil, 26 are reported for oil‐based formulations. Besides these carriers, sesame oil can resist high temperatures and UV light effects and therefore can be exploited as a sunscreen to minimize the effect of UV in different healthcare products, 27 indicating the potential of sesame oil as a valuable carrier for the formulation of biopesticides.…”
Section: Introductionmentioning
confidence: 99%